Análise por fluorescência de raios X de peças de cobre do castro de Leceia - Cardoso, João Luís (1979)
Fou pieces of the chalcolithic village of leceia (Estremadura-Portugal) have been analysed by the method of X-Ray fluorescence and revealed impurities; it is pointed out the fallibility of the conclusions based on this analysis, both in quality and quantity, of a restricted area, given the varia tion of the alloy composition in distinct zones of the same object. The pieces were described and filted in their archeological context.